High inflammogenic potential of rare earth oxide nanoparticles: the New Hazardous Entity. Issue 7 (9th August 2018) - Han, Youngju; Lee, Dong-Keon; Kim, Sung-Hyun; Lee, Seonghan; Jeon, Soyeon; Cho, Wan-Seob
Abstract: Due to the exponential increase in the development and utilization of rare earth oxide nanoparticles (REO NPs) in various fields, the possibility of exposure in humans by inhalation has increased. However, there are little information about hazards of REO NPs and its mechanisms of toxicity. In this study, we evaluated the acute pulmonary inflammation using 10 REO NPs (Dy2 O3, Er2 O3, Eu2 O3, Gd2 O3 La2 O3, Nd2 O3, Pr6 O11, Sm2 O3, Tb4 O7, and Y2 O3 ) and four well-known toxic particles (CuO, NiO, ZnO, and DQ12). Minimum three doses per NP were instilled into the lungs of female Wistar rats at surface area dose metric and lung inflammation was evaluated at 24 h post-instillation by bronchoalveolar lavage fluid (BALF) analysis and histopathological observation. All types of REO NPs showed common pathological changes including mild to moderate infiltration of neutrophils and activated macrophages in the alveoli, peribronchial, and perivascular region. The inflammogenic potential evaluated by the number of granulocytes divided by the treated surface area dose showed all types of REO NPs has much higher inflammogenic potential than DQ12, ZnO, and NiO NPs. The correlation plot between the number of granulocytes and the potential for reactive oxygen species (ROS) generation showed a good correlation with exception of Pr6 O11 . The higher inflammogenic potential of REO NPs than that of well-known highly toxic particles imply that REO NPs need special attention for inhalation exposure and more studies are needed. In addition, the potential of ROS generation is one of the key factors producing lung inflammation by REO NPs.